Enantioselective Synthesis of 2,3-Dihydrofurans Using the Catalyst of Camphor/Pinene-Based Bypiridine - Andre Anusta Barus; Chinpiao Chen (Polewali: Dewan Pengurus Daerah Sulawesi Barat Forum Dosen Indonesia, 2022)
This research describes the synthesis of two kinds of chiral ligand and their application in the cyclization of 2,3-dihydrofuran. They are camphor-based bipyridine and pinene-based bipyridine. These ligands were prepared followed the known procedure, and they were used for the enantioselective preparation of 2,3-dihydrofuran in the present of enone and ethyl bromoacetate. Ligand that gives the highest enantioselectivity value is pinene bipyridine-salt with 56% ee for cis isomer (86% yield) while 30% ee is obtained for trans isomer of 2,3-dihydrofuran (1/3).